Qualitative evaluation of antibacterial and DNA binding activity of four local ethnomedicinal plants available in Barishal, Bangladesh - Suhag, Mahmudul H; Hossain, Md Uzzal; Ahmed, Sohel; Kayes, Md Nazmul (Asian Journal of Medical and Biological Research, 2020)
Screening of antibacterial activities of plants due to secondary metabolites is an authentic basis to look for a new drug. As a result of increasing demand for traditional treatments, scientists have look forward to search the efficacy of these so called ethnomedicinal plants and have to exchange with pharmacologists. An initiative of this, the antibacterial activity of Ecliptaprostrata(L.)Mant.AzadirachtaindicaA. Juss., Aloe vera(L.)Burm.f. and Catharanthusroseus(L.) G. Don was studied against Escherichia coli and Staphylococcus aureus. Among four ethnomedicinal plants subjected to test antibacterial activities, Ecliptaprostratawas found to act against both strains of bacteria whereas Azadirachtaindicawas effective against Escherichia coli only. DNA binding affinity of these medicinal plants was also studied by viscometry. No affinity between each medicinal plant extracts and isolated human cheek cell’s DNA was observed. Asian J. Med. Biol. Res. September 2020, 6(3): 475-481